BABA-primed defense responses to Phytophthora infestans in the next vegetative progeny of potato - Floryszak-Wieczorek, Jolanta; Arasimowicz-Jelonek, Magdalena; Abramowski, Dariusz (Frontiers in Plant Science, 2015)
The transcript of the PR1 gene accumulation as an informative marker of systemic acquired resistance (SAR) was analyzed in β-aminobutyric acid (BABA) primed potato in the short-lasting (3 days) and long-lasting (28 days) time periods after induction and in the vegetative descendants of primed plants derived from tubers and from in vitro seedlings. BABA pretreatment resulted either in minimal or no PR1 gene expression, but sequential treatment with BABA followed by virulent P. infestans provided data on the imprint of post-stress information and its duration until fertilization, in the form of an enhanced PR1 transcript accumulation and a transient increase of basal resistance to the late blight disease. The primed state for defense of the susceptible potato cultivar was transmitted to its vegetative progeny as a potentiated PR1 mRNA accumulation following challenge inoculation. However,variation was observed between vegetative accessions of the BABA-primed potato genotype in responsiveness to disease. In contrast to plants derived from tubers, potato propagated through in vitro seedlings largely lost inducible resistance traits, although itretained primed PR1 gene expression.